A Simple Technique for Fast Digital Background Calibration of A/D Converters. (17th February 2008) - Centurelli Centurelli, Francesco Francesco; Monsurrò Monsurrò, Pietro Pietro; Trifiletti Trifiletti, Alessandro Alessandro
Abstract : A modification of the background digital calibration procedure for A/D converters by Li and Moon is proposed, based on a method to improve the speed of convergence and the accuracy of the calibration. The procedure exploits a colored random sequence in the calibration algorithm, and can be applied both for narrowband input signals and for baseband signals, with a slight penalty on the analog bandwidth of the converter. By improving the signal-to-calibration-noise ratio of the statistical estimation of the error parameters, our proposed technique can be employed either to improve linearity or to make the calibration procedure faster. A practical method to generate the random sequence with minimum overhead with respect to a simple PRBS is also presented. Simulations have been performed on a 14-bit pipeline A/D converter in which the first 4 stages have been calibrated, showing a 15 dB improvement in THD and SFDR for the same calibration time with respect to the original technique.